Respiratory viruses: What is their role in acute exacerbations in children with cystic fibrosis?. Issue 7 (30th March 2020) - Hizal, Mina; Yalcin, Ebru; Alp, Alpaslan; Ozden, Meltem; Karakaya, Jale; Eryilmaz Polat, Sanem; Tugcu, Gokcen; Dogru, Deniz; Ozcelik, Ugur; Kiper, Nural
Abstract: Background: Respiratory viruses (RVs) are frequently present in the airways of patients with cystic fibrosis (CF) during pulmonary exacerbations (PEx). Method and Objectives: This prospective, longitudinal study was performed to examine the role of RVs in acute exacerbations in children with CF. Sputum samples or additional midturbinate swabs were tested from all children using a polymerase chain reaction panel. The primary aims of the study were to determine the prevalence and etiologic role of RVs in exacerbations of CF and to compare changes with RV‐positive and RV‐negative infections. The secondary aims were to determine the predictive factors for RV‐related exacerbations. Results: From 50 patients with PEx, 23 (48.9%) sputum samples were virus‐positive. With a combination of sputum and swab, viral positivity increased to 56%. The virus‐positive group presented more frequently with hypoxia (oxygen saturation <93%) than the virus‐negative group ( P  = .048). Virus‐positive exacerbations were not associated with an increase in colonization rates or greater lung function decline over 12 months. Conclusions: RVs frequently present during PEx of CF. However, predicting viral infections is difficult in this group. Only the presence of hypoxia may raise the suspicion of an accompanying viral agent. The combination of sputum and nasal swab samples increases the diagnostic yield in viral infections of CF. Despite their high frequency, the presence of RVs had no impact on clinical outcomes, such as a decline in lung function and increased colonization rates.